A Nonlinear Statistical Analysis of Demand Shocks and Public Debt Dynamics in Egypt - Metwally, Diaa S.; El-Raouf, M. M. Abd; El-Qurashi, M. A.; Elshafei, Abdallah Sayed Mossalem Ahmed (Journal of Cultural Analysis and Social Change, 2025)
This study uses non-linear econometrics to analyze Egypt’s public debt from 1970-2022 and finds three key results: (1) a 89.7% debt/GDP threshold (95% CI: 87.2-92.4%) beyond which fiscal multipliers decline by 40% and interest-growth differentials become 2.5× more volatile, (2) regime asymmetries where crisis periods have 50% slower debt adjustment (α=-0.11 vs -0.32 in stable regimes) and 8.7-year persistence, and (3) institutional mediation where governance quality (Qₜ>0.6) reduces exchange rate pass-through by 40% and tourism shock impacts by 35%. On methodology side, we innovate in) debt sustainability analysis (by combining threshold VARs with Markov-switching ECMs, introducing an institutional-augmented fiscal reaction function, and estimating climate-debt linkages (∂d/∂Climate Shock=0.05). Our policy simulations show that a 1.5% GDP/year on average package of frontloaded consolidation, debt management reforms and energy subsidy rationalization is enough to reduce debt/GDP by 25-30 ppt by 2030. Getting to this requires tackling the political economy obstacles through sequential institutional reforms. When combined these results validate linear debt frameworks and provide a straightforward playbook for other emerging markets dealing with debt-institution-climate trilemmas.